Novel Strategies for Creative Learning and Education of Spirituality for Stress Management of Corporate Sector Managers (Global Journal of Management and Business Research, 2019)
We present and discuss in detail the role of Creative Teaching and Learning of Spirituality for Stress management of Corporate Sector Managers, and the need to include Spirituality in Education. The interrelationship of Creativity, Spirituality, and the Future has been explained briefly, along with Spiritual Leadership. Also, some novel strategies to achieve the objective have been described, by including the parameter of stress parameter (inversely proportional to the spiritualism level) in the innovation Equation. The paper should be useful for the corporate sector managers for reducing their stress level.
Keywords: creative teaching; learning; spirituality; stress management; spiritual leadership; novel strategies